The proteasome inhibitor Bortezomib (Velcade) as potential inhibitor of estrogen receptor‐positive breast cancer - Thaler, Sonja; Sleeman, Jonathan P. (International journal of cancer, 2015)
Around 70% of breast cancers express the estrogen receptor α (ERα) and depend on estrogen for growth, survival and disease progression. The presence of hormone sensitivity is usually associated with a favorable prognosis. Use of adjuvant anti‐endocrine therapy has significantly decreased breast cancer mortality in patients with early‐stage disease, and anti‐endocrine therapy also plays a central role in the treatment of advanced stages. However a subset of hormone receptor‐positive breast cancers do not benefit from anti‐endocrine therapy, and nearly all hormone receptor‐positive metastatic breast cancers ultimately develop resistance to anti‐hormonal therapies. Despite new insights into mechanisms of anti‐endocrine therapy resistance, e.g., crosstalk between ERα and Her2/neu, the management of advanced hormone‐receptor‐positive breast cancers that are resistant to anti‐endocrine agents remains a significant challenge. In the present study, we demonstrate that the proteasome inhibitor Bortezomib strongly inhibits ERα and HER2/neu expression, increases expression of cyclin‐dependent kinase inhibitors, inhibits expression of multiple genes associated with poor prognosis in ERα+ breast cancer patients and induces cell death in ER+ breast cancer cells in both the presence and absence of functional p53. Although Bortezomib increased the levels of p53 and increased the expression of pro‐apoptotic target genes in ERα+ breast cancer cells harboring wild‐type p53, Bortezomib also exerts anti‐tumoral effects on ERα+ breast cancer cells through suppression of ERα expression and inhibition of PI3K/Akt/mammalian target of rapamycin (mTOR) and ERK signaling independently of functional p53. These findings suggest that Bortezomib might have the potential to improve the management of anti‐endocrine therapy resistant ERα+ breast cancers independently of their p53 status.